Exploring Teachers’ Practices of Parental Involvement at ECD Level in Gilgit City - Naila Amin, Ghulam Jalani (JECCE, 2023)
This qualitative study aimed to explore teachers’ practices of parental involvement at the Early Childhood Education (ECE) level in Gilgit city. The study focused on applying Epstein’s fourteen parental involvement strategies in the schools of Gilgit city. Data were collected from sixteen teachers using a convenient sample of four schools having four ECE levels. The findings were compared first, within the same school teachers, then across the school teachers against each question. Results indicated that teachers use diverse strategies for parental involvement to help their children read, listen, and write. Strategies are also diversified in terms of class level and schools. The majority of the teacher’s design projects, assign home projects, make models, and color, cut, and paste different collections. However, there is a lack of awareness about making sure parents are effectively involved in the ECD level.